Conjugation with L, L-diphenylalanine Self-Assemblies Enhances In Vitro Antitumor Activity of Phthalocyanine Photosensitizer. Issue 1 (December 2017) - Souza, Márcia; Prieto, Tatiana; Rodrigues, Tiago; Ferreira, Fabio; Nascimento, Francisco; Ribeiro, Anderson; Silva, Emerson; Giuntini, Francesca; Alves, Wendel
Abstract We present the synthesis and characterization of new peptide conjugates obtained by hierarchical co-assembly of L, L-diphenylalanine (FF) and zinc phthalocyanine complexes (ZnPc) in water. Self-assembly capabilities under defined conditions were investigated by scanning electron microscopy, and photophysical properties were evaluated using UV-Vis and fluorescence spectroscopy. AFM observations demonstrated that these ZnPcs form different highly ordered arrays on the crystalline faces of the FF microplates and that surface roughness significantly changes with the presence of differently substituted phthalocyanine units. XRD assays showed that the overall molecular packing of the conjugates is organized according to a hexagonal symmetry, with ZnPcs hosted in the interstices of the peptide phase.In vitro photodynamic studies were conducted on human breast cancer MCF-7 cells to investigate both cellular uptake and cytotoxicity. It was shown that FF self-assemblies are not toxicity and enhance accumulation of ZnPc in MCF-7 cells, improving apoptotic cell death upon irradiation. Our findings demonstrate enhancement of ZnPc antitumor efficiency by FF conjugates and a proof-of-concept for new photosensitizer carriers based on peptide conjugates.